Response of the Arctic Marine Inorganic Carbon System to Ice Algae and Under‐Ice Phytoplankton Blooms: A Case Study Along the Fast‐Ice Edge of Baffin Bay. Issue 2 (27th February 2019) - Else, Brent G. T.; Whitehead, Jeremy J.; Galindo, Virginie; Ferland, Joannie; Mundy, C. J.; Gonski, Stephen F.; Ehn, Jens K.; Rysgaard, Søren; Babin, Marcel
Abstract: Past research in seasonally ice‐covered Arctic seas has suggested that ice algae play a role in reducing dissolved inorganic carbon (DIC) during spring, preconditioning surface waters to low dissolved CO2 ( p CO2sw ), and uptake of atmospheric CO2 during the ice‐free season. The potential role of under‐ice phytoplankton blooms on DIC and p CO2sw has not often been considered. In this study we examined the inorganic carbon system beneath landfast sea ice starting midway through a bottom ice algae bloom and concluding in the early stages of an under‐ice phytoplankton bloom. During most of the ice algae bloom we observed a slight increase in DIC/ p CO2sw in surface waters, as opposed to the expected reduction. Biomass calculations confirm that the role of ice algae on DIC/ p CO2sw in the study region were minor and that this null result may be widely applicable. During snow melt, we observed an under‐ice phytoplankton bloom (to 10 mg/m 3 Chl a ) that did reduce DIC and p CO2sw . We conclude that under‐ice phytoplankton blooms are an important biological mechanism that may predispose some Arctic seas to act as a CO2 sink at the time of ice breakup. We also found that p CO2sw was undersaturated at the study location even at the beginning of our sampling period, consistent with several other studies that have measured under‐ice p CO2sw in late winter or early spring. Finally, we present the first measurements of carbonate saturation states for this region, which may be useful for assessing the vulnerability of a local soft‐shelled clam fishery to ocean acidification. Key Points: An ice algae bloom beneath landfast sea ice did not impact DIC/pCO2, and is not expected to contribute to CO2 uptake from the atmosphere Under ice phytoplankton blooms did significantly reduce DIC/pCO2, likely making the region a stronger sink for atmospheric CO2 at break‐up Arctic seas do not often experience supersaturation of pCO2 during the Arctic winter